1987
DOI: 10.1093/jn/117.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Clarification and Quantitation of Primary (Tissue) and Secondary (Microbial) Catabolites of Riboflavin That Are Excreted in Mammalian (Rat) Urine

Abstract: Riboflavin derivatives were quantitated and identified in urine of rats fed 0, 2 and 6 micrograms riboflavin/g diet per day both with and without added succinyl sulfathiazole for 6 wk. Two rats from each dietary group were placed in metabolic cages and urine was collected in the dark for 24 h. On the fourth week, a third animal from each group received an i.p. injection of [2-14C]riboflavin before being placed in a metabolic cage and urine collected in the dark for 48 h. Urine samples were extracted with pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This apparent discrepancy between in vitro and in vivo , was not due to toxic effects of RF in melanoma cells, but might be due to the metabolization of RF in vivo , which also provides photoproducts as main catabolites. It has been shown by Ohkawa et al (1983) [35] and Chastain and McCormick (1987) [36] that RF photodecomposition can occur in the human body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent discrepancy between in vitro and in vivo , was not due to toxic effects of RF in melanoma cells, but might be due to the metabolization of RF in vivo , which also provides photoproducts as main catabolites. It has been shown by Ohkawa et al (1983) [35] and Chastain and McCormick (1987) [36] that RF photodecomposition can occur in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by Ohkawa et al (1983) [35] and Chastain and McCormick (1987) [36] that RF photodecomposition can occur in situ in the human body. Our group showed that irradiated RF (iRF) has a strong anti-tumoral effect on leukemia cells [37], as well as anti-proliferative and anti-metastatic effects on solid tumors [34].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, flavocoenzymes are not covalently attached to apoproteins but form noncovalent complexes (4). Flavin metabolites other than riboflavin, FMN, and FAD were identified in human plasma and urine by McCormick and coworkers (5)(6)(7)(8), but these metabolites probably lack biologic activity.…”
Section: Introductionmentioning
confidence: 99%
“…When this vitamin is irradiated with light at wavelengths that are in the visible range (and hence is not absorbed by simple proteins), the flavin excited state can interact with nucleic acids contained within viral and bacterial pathogens to effect photo-oxidation, especially of guanine residues, to cause killing of such organisms. The side-chain photoproducts of riboflavin that result are mainly those that we have shown are excreted in urine (Chastain & McCormick, 1987a,b, 1988 and are secreted in milk from cows (Roughead & McCormick, 1990a) and human subjects (Roughead & McCormick, 1990b). Fig.…”
Section: Pathogen Photoinactivationmentioning
confidence: 74%